The readers of Broken Wheel recommend - Bivald, Katarina, 1983- (Sourcebooks Landmark, 2016)
"Broken Wheel, Iowa, has never seen anyone like Sara, who traveled all the way from Sweden just to meet her pen pal, Amy. When she arrives, however, she finds that Amy's funeral has just ended. Luckily, the townspeople are happy to look after their bewildered tourist--even if they don't understand her peculiar need for books. Marooned in a farm town that's almost beyond repair, Sara starts a bookstore in honor of her friend's memory. All she wants is to share the books she loves with the citizens of Broken Wheel and to convince them that reading is one of the great joys of life. But she makes some unconventional choices that could force a lot of secrets into the open and change things for everyone in town. Reminiscent of The Guernsey Literary and Potato Peel Pie Society, this is a warm, witty book about friendship, stories, and love" --